Genetic investigation of equine recurrent uveitis in Appaloosa horses. (2nd December 2019) - Rockwell, H.; Mack, M.; Famula, T.; Sandmeyer, L.; Bauer, B.; Dwyer, A.; Lassaline, M.; Beeson, S.; Archer, S.; McCue, M.; Bellone, R. R.
Summary: Equine recurrent uveitis (ERU) is characterized by intraocular inflammation that often leads to blindness in horses. Appaloosas are more likely than any other breed to develop insidious ERU, distinguished by low‐grade chronic intraocular inflammation, suggesting a genetic predisposition. Appaloosas are known for their white coat spotting patterns caused by the leopard complex spotting allele ( LP ) and the modifier PATN1 . A marker linked to LP on ECA1 and markers near MHC on ECA20 were previously associated with increased ERU risk. This study aims to further investigate these loci and identify additional genetic risk factors. A GWAS was performed using the Illumina Equine SNP70 BeadChip in 91 horses. Additive mixed model approaches were used to correct for relatedness. Although they do not reach a strict Bonferroni genome‐wide significance threshold, two SNPs on ECA1 and one SNP each on ECA12 and ECA29 were among the highest ranking SNPs and thus warranted further analysis ( P = 1.20 × 10 −5, P = 5.91 × 10 −6, P = 4.91 × 10 −5, P = 6.46 × 10 −5 ). In a second cohort ( n = 98), only an association with the LP allele on ECA1 was replicated ( P = 5.33 × 10 −5 ). Modeling disease risk with LP, age and additional depigmentation factors ( PATN1 genotype and extent of roaning) supports an additive role for LP and suggests an additive role for PATN1 . Genotyping for LP and PATN1 may help predict ERU risk (AUC = 0.83). The functional role of LP and PATN1 in ERU development requires further investigation. Testing samples across breeds with leopard complex spotting patterns and a denser set of markers is warranted to further refine the genetic components of ERU.